Multicenter Prospective Cohort Study of Renal Failure in Patients Treated with Colistin versus Polymyxin B - Rigatto, Maria Helena (Antimicrob Agents Chemother, 2016)
Nephrotoxicity is the main adverse effect of colistin and polymyxin B (PMB). It is not clear whether these two antibiotics are associated with different nephrotoxicity rates. We compared the incidences of renal failure (RF) in patients treated with colistimethate sodium (CMS) or PMB for ≥48 h. A multicenter prospective cohort study was performed that included patients aged ≥18 years. The primary outcome was renal failure (RF) according to Risk, Injury, Failure, Loss, and End-stage renal disease (RIFLE) criteria. Multivariate analysis with a Cox regression model was performed. A total of 491 patients were included: 81 in the CMS group and 410 in the PMB group. The mean daily doses in milligrams per kilogram of body weight were 4.2 ± 1.3 and 2.4 ± 0.73 of colistin base activity and PMB, respectively. The overall incidence of RF was 16.9% (83 patients): 38.3% and 12.7% in the CMS and PMB groups, respectively (P < 0.001). In multivariate analysis, CMS therapy was an independent risk factor for RF (hazard ratio, 3.35; 95% confidence interval, 2.05 to 5.48; P < 0.001) along with intensive care unit admission, higher weight, older age, and bloodstream and intraabdominal infections. CMS was also independently associated with a higher risk of RF in various subgroup analyses. The incidence of RF was higher in the CMS group regardless of the patient baseline creatinine clearance. The development of RF during therapy was not associated with 30-day mortality in multivariate analysis. CMS was associated with significantly higher rates of RF than those of PMB. Further studies are required to confirm our findings in other patient populations.